Preliminary Study on the Development of Global Warming E-Learning Material in Independent Curriculum - Mela Femilia; Asrizal Asrizal (Universitas Negeri Padang, 2023)
Twenty first century education promotes the use of communication technology in learning. Electronic teaching materials are the application of communication technology in learning activities. However, the application of electronic teaching materials in the independent curriculum were still limited. The solution that can be done was to do a preliminary study. Preliminary study need to be carried out to analyze learning problems, students, learning objectives, and learning settings. This type of research is descriptive research. Data obtained using instruments in the form of interviews, questionnaires, and documentation. The data analysis technique used is descriptive statistical analysis. Based on data analysis, it can be stated that there are four results of this study. First, the problems experienced by teachers are designing content and variations in thinking skills in the sufficient category, enriching learning experiences using teaching materials in the sufficient category, adequacy and equitable evaluation of learning in the sufficient category. Second, the characteristics of students on global warming material are generally good. Third, the results of the analysis of learning objectives show competence in the appropriate category, content in the appropriate category, variations in the very appropriate category, and operational verb in the sufficient category. Fourth, the results of the analysis of learning settings are in the inappropriate category. Therefore, the results of this study can be used as a basis for developing electronic teaching materials according to the independent curriculum.